Lattice Gauge Theories An Introduction (Fourth Edition) - Rothe, Heinz J (World Scientific Lecture Notes In Physics, 2012)
This book provides a broad introduction to gauge field theories formulated on a space-time lattice, and in particular of QCD. It serves as a textbook for advanced graduate students, and also provides the reader with the necessary analytical and numerical techniques to carry out research on his own. Although the analytic calculations are sometimes quite demanding and go beyond an introduction, they are discussed in sufficient detail, so that the reader can fill in the missing steps. The book also introduces the reader to interesting problems which are currently under intensive investigation. Whenever possible, the main ideas are exemplified in simple models, before extending them to realistic theories. Special emphasis is placed on numerical results obtained from pioneering work. These are displayed in a great number of figures. Beyond the necessary amendments and slight extensions of some sections in the third edition, the fourth edition includes an expanded section on Calorons - a subject which has been under intensive investigation during the last twelve years.